The Effectiveness of Personalized Bowel Preparation Using a Smartphone Camera Application: A Randomized Pilot Study - Jae won Jung; Jongha Park; Gi Jung Jeon; Young Soo Moon; Sung Yuon Yang; Tae Oh Kim; Eui Tay Jung; Hee-Cheol Kim (Gastroenterology Research and Practice)
Background. We aimed to investigate the effectiveness of a smartphone application that analyzes and judges the optimal dosage of polyethylene glycol (PEG) for bowel preparation. Methods. Patients were assigned to use the smartphone camera application (app group) or written instructions (non-app group). The smartphone camera application was programmed to analyze the bowel preparation quality and automatically determine the dosage of PEG from an analysis of stool images. In contrast, the non-app group consumed PEG solution according to the manual. Results. The primary outcome was the quality of the bowel preparation based on blinded ratings using the Ottawa bowel preparation scale (OBPS). There was no statistically significant difference in the mean OBPS scores between the two groups (P=0.950). However, the app group consumed a lower dose of PEG than the non-app group (mean dosage (mL): 3713.2 ± 405.8 versus 3979.2 ± 102.06, P=0.001). The app group (5-point Likert scale; mean score 4.37 ± 0.895) had high acceptance of the application. Conclusions. Although the app group consumed a lower PEG dose, the bowel preparation quality was similar in the two groups. Moreover, use of the smartphone camera application enhanced compliance with the bowel preparation.